Personal skills for optimal identity development: A person-centered approach in Italian late-adolescents. - Luigia Simona Sica; Laura Aleni Sestito (Journal for Person-Oriented Research, 2021)
The present study examined the association between identity statuses and some competences such as creativity, personal growth initiative and agency, which can actually be considered as resources for the development of optimal identity in our de-standardized society (personal skills for optimal identity development, PSID). Participants were 250 adolescents (118 males and 132 females) attending the last two years of various high schools in Italy. We used five self-report measures of identity development, agency, creativity, and personal growth initiative, and specific psychosocial correlates (anxiety, depression and well-being) to examine the association between identity, PSID and both well- and ill-being. Based on a person- centered approach, five typologies were obtained in order to describe the differentiated interplay between identity and PSID. Our findings suggested that late adolescents showing medium/high levels of PSID seem to be more advanced in their identity definition; as a result, they show positive psycho-social functioning, supporting the hypothesis that PSID can allow the acquisition of optimal identity. Suggestions for developing interventions to foster personal resources in this age group are discussed.